2022
DOI: 10.1097/aci.0000000000000857
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the case for intralymphatic immunotherapy

Abstract: Purpose of reviewIntralymphatic immunotherapy (ILIT) is a promising novel method of immunotherapy, that is short and convenient, and may be very effective. Results have been varied, and efforts to unravel the real value of the treatment are ongoing. Methods used to assess the effect in clinical trials have been so varied that it is difficult to compare studies with each other.Recent findingsSome advances have been made; the importance of injecting into the lymph node has been illustrated, and treatment with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…Compelling evidence has demonstrated that subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT), as well as oral immunotherapy for the management of food allergies show safety and efficacy for many allergic patients [190]. Other alternative routes of administration such as epicutaneous immunotherapy or direct injection into lymph nodes (intralymphatic immunotherapy), have been explored to attempt to improve safety and patients’ convenience while maintaining efficacy [191, 192].…”
Section: Allergen-specific Immunotherapymentioning
confidence: 99%
“…Compelling evidence has demonstrated that subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT), as well as oral immunotherapy for the management of food allergies show safety and efficacy for many allergic patients [190]. Other alternative routes of administration such as epicutaneous immunotherapy or direct injection into lymph nodes (intralymphatic immunotherapy), have been explored to attempt to improve safety and patients’ convenience while maintaining efficacy [191, 192].…”
Section: Allergen-specific Immunotherapymentioning
confidence: 99%
“…However, the same year a Malaysian meta-analysis of 11 trials found ILIT to be safe but not effective; high variation amongst the trials may have contributed to this finding [66]. The following year, 2022, a Danish review and meta-analysis of 14 studies, including our first double-blind randomised clinical trial published in 2022 [67], found that injecting allergen directly into a lymph node strengthens the protective immune response, is safe, induces desensitisation, and very likely induces tolerance as well [68]. A Chinese metaanalysis from 2023 [69] concludes that for individuals with AR, ILIT is safe and effective.…”
Section: Ilit Reviews and Meta-analysesmentioning
confidence: 99%
“…To the Editor, Relevant symptom-reducing effect of intra-lymphatic immunotherapy, ILIT, previously found in clinical trials 1 has recently been reviewed. 2 The review contains three meta-analyses; one found ILIT safe but not effective, whereas two studies found ILIT to be safe and effective in the first year of treatment. In ILIT allergen is injected directly into a lymph node to reduce symptom response to the culprit allergen.…”
Section: Ultrasound-guided Intralymphatic Immunotherapy: a Single-cen...mentioning
confidence: 99%